2017
DOI: 10.1111/iep.12234
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of bone marrow downregulation in brain‐dead rats

Abstract: Experimental findings support the evidence of a persistent leucopenia triggered by brain death (BD). This study aimed to investigate leucocyte behaviour in bone marrow and blood after BD in rats. BD was induced using intracranial balloon catheter inflation. Sham-operated (SH) rats were trepanned only. Thereafter bone marrow cells were harvested every six hours from the femoral cavity and used for total and differential counts. They were analysed further by flow cytometry to characterize lymphocyte subsets, gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(79 reference statements)
0
1
0
1
Order By: Relevance
“…These results are consistent with those in several articles that describe arterial hypotension during BD, which occurs due to autonomic discharge followed by intense vasodilation. Studies have shown that after 1 h of BD, the blood pressure levels were comparable to those of SHAM animals (control) 14 17 .…”
Section: Discussionmentioning
confidence: 83%
“…These results are consistent with those in several articles that describe arterial hypotension during BD, which occurs due to autonomic discharge followed by intense vasodilation. Studies have shown that after 1 h of BD, the blood pressure levels were comparable to those of SHAM animals (control) 14 17 .…”
Section: Discussionmentioning
confidence: 83%
“…Considerando que a inflamação sistêmica deflagrada pela morte encefálica em ratos machos está associada, de modo paradoxal, à leucopenia persistente (Simas et al, 2012a) e que a redução da atividade da medula óssea não está relacionada a alterações na expressão de moléculas de adesão granulocíticas (Menegat et al, 2017), sugere-se que a inflamação sistêmica e progressiva observada em doadores em morte encefálica depende, essencialmente, da ativação da célula endotelial.…”
Section: Discussionunclassified